2020
DOI: 10.1177/1943387520924515
|View full text |Cite
|
Sign up to set email alerts
|

Review of Orbital Fractures in an Urban Level I Trauma Center

Abstract: Objective: To perform a comprehensive review and analysis of surgically treated orbital fractures. Study Design: Retrospective cohort chart review study for surgically treated orbital fractures during 5 years. Results: A total of 173 patients (average age 41.6 years) were diagnosed with orbital fractures. Most were male with a ratio of 3.3:1. Most fractures were caused by assault (39.3%); 22.5% of the cases were bilateral. The left orbit (40.5%) was fractured more than the right. The orbital floor (97.1%) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…As the orbit is an important aesthetic component of the face, fracture repair surgery faces certain challenges, and its complications often cause aesthetic and functional concerns (44,45). The timing and approach of surgery for orbital fractures has been widely debated, with some authors suggesting that conservative management is more beneficial than early surgical intervention (46).…”
Section: Discussionmentioning
confidence: 99%
“…As the orbit is an important aesthetic component of the face, fracture repair surgery faces certain challenges, and its complications often cause aesthetic and functional concerns (44,45). The timing and approach of surgery for orbital fractures has been widely debated, with some authors suggesting that conservative management is more beneficial than early surgical intervention (46).…”
Section: Discussionmentioning
confidence: 99%
“…This demographic profile is consistent with the current literature on assault-related orbital fractures. 8,16–40…”
Section: Discussionmentioning
confidence: 99%
“…Although the rates of causes of injuries are affected by socioeconomic and demographic characteristics of the target population, 52 recent large population studies performed in the US, UK, Italy, and Germany showed that assault is the most common mechanism of injury, followed by falls and traffic accidents. [52][53][54][55][56][57] In Japan, assault is a less common mechanism of injury, while falls and sports are the more common ones. 51 Since the safety for driving is improving due to advanced technology, the rate of traffic accidents is gradually decreasing.…”
Section: Causes Of Injuriesmentioning
confidence: 99%